2006
DOI: 10.1007/s10484-006-9008-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emotional Distance on Psychophysiologic Concordance and Perceived Empathy Between Patient and Interviewer

Abstract: This preliminary study investigated the effect of emotional distance on psychophysiologic concordance and perceived empathy in a clinical population. Participants included 20 adult outpatients from a mental health clinic that underwent a brief semi-structured interview with a trained psychiatrist in either an emotionally neutral or an emotionally distant condition. Simultaneous skin conductance (SC) levels of the patient and interviewer were recorded and used to calculate a measure of psychophysiologic concord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 53 publications
(53 reference statements)
2
110
1
Order By: Relevance
“…Hence, instead of calculating cross correlation over the signals themselves, they are calculated over sets of slopes. This has been called the concordance score by Marci and colleagues [113,114]. Using multiple modalities can significantly increase the performance of similarity measurement.…”
Section: Emotional Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, instead of calculating cross correlation over the signals themselves, they are calculated over sets of slopes. This has been called the concordance score by Marci and colleagues [113,114]. Using multiple modalities can significantly increase the performance of similarity measurement.…”
Section: Emotional Convergencementioning
confidence: 99%
“…One way (among others) to improve empathy in human interaction could be through technological innovations that can measure and take into account empathy [109,113]. Such technologies might make empathy a more salient and influential construct in human interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption appears to only sometimes be true. Physiological synchrony is associated with both beneficial relational outcomes such as empathy (Marci & Orr, 2006), enhanced group performance (Elkins, Muth, Hoover, Walker, Carpenter, & Switzer, 2009), and increased social presence (Chanel et al, 2012), but also detrimental relational outcomes such as marital dissatisfaction (Levenson & Gottman, 1983) and mutual dislike (Kaplan, Burch, & Bloom, 1964). In order to disentangle the meaning of physiological synchrony, self-report and behavioral measures are critical to triangulating the interpersonal meaning of this internally shared state (Palumbo, et al, 2016).…”
Section: Physiological Synchronymentioning
confidence: 99%
“…The SNS is typically associated with engagement in a task or situation (Blascovich, Mendes, Tomaka, Salomon, & Seery, 2003;Seery, 2011). Covariation of the sympathetic nervous system was the first form of physiological synchrony observed in the lab (Kaplan & Bloom, 1960), and it has been widely studied in the physiological synchrony literature (Levenson & Gottman, 1983;Marci & Orr, 2006). Especially because SNS activation reflects engagement in a situation, sympathetic covariation during social interactions is thought to reflect a shared internal state (Levenson & Gottman, 1983).…”
Section: Physiological Synchronymentioning
confidence: 99%
“…Furthermore, results from dyadic relationship studies employing infant-mother (Cohn and Tronick 1988), patient-clinician (Marci and Orr 2006), or marital dyads (Levenson and Ruef 1992) have suggested that similarities in psychophysiological responses may improve social closeness. For example, physiological concordance between clients and therapists has been associated with higher evaluation of therapists' empathy by the clients (Marci et al 2007).…”
Section: Introductionmentioning
confidence: 99%